Alertas de mantenimiento vehicular y localización de talleres mecánicos mediante una aplicación web con georrereferenciación - Vélez Moya, Tammy Karina (2015)
The rate of growth of the economy in the Ecuador has gone evolving little by little, and this event has taken to that the population has access to the acquisition of goods furniture making that the self-driven park increases every day. At the present time the places web are from a lot of help to the moment to automate the processes that people carry out in their daily life. In the City of Quevedo specialized shops that possess the necessary resources to give maintenance to the vehicles exist and that many of the citizens don't know due to the diffusion lack on the part of the owners of these establishments. It is necessary to indicate that this type of virtual place doesn't exist in our means. The constitution of the Ecuador in the I articulate 14 he/she mentions the following thing: "The population's right is recognized to live in a healthy and ecologically balanced atmosphere that guarantees the sustainability and the good one to live, sumakkawsay. It is declared of public interest the preservation of the atmosphere, the conservation of the ecosystems, the biodiversity and the integrity of the genetic patrimony of the country, the prevention of the environmental damage and the recovery of the degraded natural spaces." For such a reason in this investigation project one has like goal to take a preventive maintenance of the vehicles that you/they are associated with our technological net, for it will be implemented it an application web that allows to give alarms to the users on the maintenance that he/she should carry out to their car.